Effect of preoperative immunonutrition on complications after salvage surgery in head and neck cancer - Simon Andreas Mueller; Catherine Mayer; Beat Bojaxhiu; Carla Aeberhard; Philipp Schuetz; Zeno Stanga; Roland Giger (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Patients undergoing salvage surgery for recurrent head and neck squamous cell carcinoma are at high risk of postoperative complications due to the adverse effects of radiotherapy on wound healing. Malnutrition is an additional risk factor and we tested the hypothesis that preoperative administration of immunonutrition would decrease complications in this high risk population. Methods This single armed study with historical control included consecutive patients undergoing salvage surgery for recurrent head and neck squamous cell carcinoma. We compared outcomes before and after implementation of preoperative immunonutrition and adjusted the regression analysis for gender, age, body mass index, Nutritional Risk Screening (NRS 2002), tobacco and alcohol consumption, tumor localization, tumor stage, and type of surgery. The primary endpoint was overall complications from surgery within a follow-up of 30 days. Results Ninety-six patients were included (intervention group: 51, control group: 45). Use of preoperative immunonutrition was associated with a significant reduction in overall complications (35% vs. 58%, fully-adjusted odds ratio 0.30 (95%CI 0.10–0.91, p = 0.034). Length of hospital stay was also significantly reduced (17 days vs. 6 days, p = < 0.001). No differences in mortality and hospital readmission were found. These results remained robust in multivariate analysis. Conclusions In patients undergoing salvage surgery for recurrent head and neck squamous cell carcinoma, preoperative immunonutrition exhibited favorable effects on the complication rate and consequently reduced the length of hospital stay. By improving both tissue regeneration and immune response, immunonutrition may help to improve surgical outcomes in this high-risk population.